2018
DOI: 10.3390/batteries4040062
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Ion Complexes and Their Impact on Charge Transport in Organic Solvent-Based Electrolyte Solutions for Lithium Batteries: Insights from a Theoretical Perspective

Abstract: Electrolyte formulations in standard lithium ion and lithium metal batteries are complex mixtures of various components. In this article, we review molecular key principles of ion complexes in multicomponent electrolyte solutions in regards of their influence on charge transport mechanisms. We outline basic concepts for the description of ion–solvent and ion–ion interactions, which can be used to rationalize recent experimental and numerical findings concerning modern electrolyte formulations. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 172 publications
(455 reference statements)
4
81
0
Order By: Relevance
“…All studies reveal significant ordering effects when compared to bulk phase due to the polarity of water molecules. Hence, and in agreement with experimental findings, a reasonable assumption for highly polar solvents like water due to charge-induced ordering effects reads M 2 trans (r) < M 2 trans which reveals a decreased local dielectric constant in presence of charged species when compared to pure solvents [34,50]. In consequence, the local dielectric constant is lower when compared to the bulk dielectric constant in accordance with r (r) < , which means that electrostatic effects become more pronounced for polar solvents in close distance to charged interfaces.…”
Section: Dielectric Decrement Effectssupporting
confidence: 87%
See 4 more Smart Citations
“…All studies reveal significant ordering effects when compared to bulk phase due to the polarity of water molecules. Hence, and in agreement with experimental findings, a reasonable assumption for highly polar solvents like water due to charge-induced ordering effects reads M 2 trans (r) < M 2 trans which reveals a decreased local dielectric constant in presence of charged species when compared to pure solvents [34,50]. In consequence, the local dielectric constant is lower when compared to the bulk dielectric constant in accordance with r (r) < , which means that electrostatic effects become more pronounced for polar solvents in close distance to charged interfaces.…”
Section: Dielectric Decrement Effectssupporting
confidence: 87%
“…In contrast to previous mean field considerations as discussed in the last section, it was shown that specifically the molecular interactions between the polyelectrolyte, the ions as well as the solvent molecules play a crucial role [34]. In this section, we will concentrate on the influence of solvent-related contributions in more detail.…”
Section: Solvent Effectsmentioning
confidence: 92%
See 3 more Smart Citations